A Pressing Need for Gender Balance in AGU Honors Nominations. Issue 9 (4th March 2014) - Ball, Jessica
<x xml:space="preserve">Abstract</x> AGU thrives on the volunteer efforts of its scientists, which is how I found myself agreeing to be a member of AGU's Science for Solutions Award committee last year. The award is targeted specifically at students and postdoctoral scientists who use Earth and space science to solve societal problems, and it was an intriguing experience to go through the process of evaluating the nominees and selecting a winner. All across the Union, members of other honors committees were going through a similar process, and at the 2013 Fall Meeting, those award recipients selected by the committees were honored.